Sensitive and Repeatable Photoinduced Luminescent Radicals from A Simple Organic Crystal - Mu, Yingxiao; Liu, Yanyan; Tian, Haiyan; Ou, Depei; Gong, Li; Zhao, Juan; Zhang, Yi; Huo, Yanping; Yang, Zhiyong; Chi, Zhenguo (Angewandte Chemie International Edition, 2021)
Photoinduced organic radicals are important for chemical and physical processes of organic materials, which are extensively investigated and applied in organic synthesis, photoelectronic devices and biotechnology. However, there are rare reports of the luminescence for these photoinduced radicals, especially in the condensed state. Herein, an unexpected and interesting luminescent radical is described, which can be rapidly and reversibly generated from a simple organic crystal by gentle light irradiation in air. It was revealed that the twist and asymmetric conformation of isolated molecule in its crystal with only weak C−H⋅⋅⋅π intermolecular interactions, which led to the generation of such photoinduced luminescent radicals. In addition, dual‐channel photosensitive device with rapid response and well repeatability can be obtained based on the thin film of this organic crystal, showing both photoswitching on luminescence and conducting. Simultaneous dual‐channel switching of luminescence and conducting can be achieved from a simple organic crystal by UV irradiation, which is because of the sensitive and repeatable generation of photoinduced luminescent radicals inside.